Effects of the COVID-19 Pandemic on Patients With NMO Spectrum Disorders and MOG-Antibody–Associated Diseases: COPANMO(G)-Study. Issue 2 (24th March 2023) - Hümmert, Martin W.; Bütow, Franziska; Tkachenko, Daria; Ayzenberg, Ilya; Pakeerathan, Thivya; Hellwig, Kerstin; Klotz, Luisa; Häußler, Vivien; Stellmann, Jan-Patrick; Warnke, Clemens; Goereci, Yasemin; Etgen, Thorleif; et al.
Abstract : Background and Objectives: To evaluate the effects of the coronavirus disease 2019 (COVID-19) pandemic on the life of patients with neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody–associated diseases (MOGAD). Methods: This multicenter, cross-sectional study included data of 187 patients recruited from 19 different German and Austrian Neuromyelitis Optica Study Group (NEMOS) centers between July 2021 and March 2022. The effects of the pandemic on immunotherapeutic treatment and access to care, the possible severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and the potential effect of vaccination against SARS-CoV-2 on disease incidence and relapse risk were assessed using a patient questionnaire. Health-related quality of life (HRQoL) was measured with the EuroQoL Group 5-Dimension 5-Level Scale (EQ-5D-5L). Demographic and clinical characteristics were retrieved from the NEMOS database. Results: One hundred eighty-seven patients (75% women; median age 47 [range 21–86] years; median disease duration 5.5 [range 0–67] years; median Expanded Disability Status Scale 2.0 [range 0–8.0]; 51% aquaporin-4 immunoglobulin G (AQP4-IgG)-positive, 36% myelin oligodendrocyte glycoprotein (MOG)-IgG-positive 13% double-seronegative) were analyzed. Most patients maintained excellent access to healthcare services throughout the pandemic. Immunotherapy was not changed in 88% of patients. Ninety-one percent of all patients were satisfied with medical care during the pandemic. Nearly two-thirds (64%) of patients rated their risk of infection with SARS-CoV-2 as low or moderate. Among this study sample, 23 patients (12%) knowingly acquired an infection with SARS-CoV-2 and predominantly had a nonsevere course of illness (n = 22/23, 96%). The SARS-CoV-2 vaccination rate was 89%, with 4 cases of confirmed attack or first manifestation of NMOSD/MOGAD occurring in temporal association with the vaccination (range 2–9 days). The reported HRQoL did not decline compared with a prepandemic assessment (mean EQ-5D-5L index value 0.76, 95% bootstrap confidence interval [CI] 0.72–0.80; mean EQ-VAS 66.5, 95% bootstrap CI 63.5–69.3). Discussion: This study demonstrates that, overall, patients with NMOSD/MOGAD affiliated with specialized centers received ongoing medical care during the pandemic. Patients' satisfaction with medical care and HRQoL did not decrease.